Growth in the Shadow of Expropriation * - Aguiar, Mark; Amador, Manuel (Quarterly Journal of Economics, 2011)
We propose a tractable variant of the open economy neoclassical growth model that emphasizes political economy and contracting frictions. The political economy frictions involve a preference for immediate spending, while the contracting friction is a lack of commitment regarding foreign debt and expropriation. We show that the political economy frictions slow an economy's convergence to the steady state due to the endogenous evolution of capital taxation. The model rationalizes why openness has different implications for growth depending on the political environment, why institutions such as the treatment of capital income evolve over time, why governments in countries that grow rapidly accumulate net foreign assets rather than liabilities, and why foreign aid may not affect growth.